2011
DOI: 10.1074/jbc.m111.218669
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogaster Myosin-18 Represents a Highly Divergent Motor with Actin Tethering Properties

Abstract: The gene encoding Drosophila myosin-18 is complex and can potentially yield six alternatively spliced mRNAs. One of the major features of this myosin is an N-terminal PDZ domain that is included in some of the predicted alternatively spliced products. To explore the biochemical properties of this protein, we engineered two minimal motor domain (MMD)-like constructs, one that contains the N-terminal PDZ (myosin-18 M-PDZ) domain and one that does not (myosin-18 M-ΔPDZ). These two constructs were expressed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 56 publications
4
46
0
Order By: Relevance
“…Mammalian myosin-18A␣-S1 in the absence of nucleotide binds actin with an affinity (K d ϳ5.0 M) similar to that previously reported for the isoforms of D. melanogaster myosin-18 (15). Mammalian myosin-18A␤, however, exhibits a lower actin affinity around 50 M. The higher affinity of the myosin-18A␣ isoform is probably related to the actin binding sequence located in the extended N-terminal region between the PDZ domain and the KE-rich region of that isoform (14).…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Mammalian myosin-18A␣-S1 in the absence of nucleotide binds actin with an affinity (K d ϳ5.0 M) similar to that previously reported for the isoforms of D. melanogaster myosin-18 (15). Mammalian myosin-18A␤, however, exhibits a lower actin affinity around 50 M. The higher affinity of the myosin-18A␣ isoform is probably related to the actin binding sequence located in the extended N-terminal region between the PDZ domain and the KE-rich region of that isoform (14).…”
Section: Discussionsupporting
confidence: 58%
“…Class-18 myosins represent the extreme edge of this diversity. Previous work demonstrated that D. melanogaster myosin-18 bound ATP poorly and showed no evidence for an ATPase activity and that it bound actin in an ATP-insensitive manner (15). Earlier biochemical studies using myosin-18A fragments expressed in mammalian cells suggested that it may lack the enzymatic activity that is usually associated with myosins and may function more like an actin-binding protein than as a motor protein, although enzymatic measurements were not directly performed (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations